Some aspects of biology and fishery of walleye pollock Theragra chalcogramma in the southwestern Chukchi Sea relative to the size and age structure - A. V. Buslov; E. E. Ovsyannikov (Известия ТИНРО)
Catch distribution and size-age structure of walleye pollock in the Chukchi Sea are considered on the data obtained in surveys conducted by TINRO in 2018–2020. The age of pollock was determined by otoliths. Two age groups were presented in the catches: the first group of juveniles and 1-year old fish and the second group of 7–22-year old fish, mostly 8–15 years old (90 %). The fish of 3–6 year old were absent in the catches. This age structure suggests that the stock is formed by the fish migrated from the northern Bering Sea. However, the backward migration is doubtful; the pollock, once migrated to the Chukchi Sea, remain in this new habitat, as could be seen from the age-length dependence for a part of the stock distinguished by lower growth rate because of dwelling in severe conditions of this area. Aggregations of the fast-growing (just migrated from the Bering Sea) and slow-growing (local residents) pollock had different distribution patterns in the surveyed area in the southwestern Chukchi Sea. The fast-growing allochthonous pollock distributed widely, including the seaward waters, whereas the resident pollock preferred the coastal waters. The walleye pollock fishery has started in the southern coastal area of the Chukchi Sea in 2021, so the resident stock is exploited mainly.